Leprosy and Lack of Awareness in U.S. Clinicians. Issue 5 (September 2016) - Bianchi, Terri; Sevigny, Gina
Abstract : ABSTRACT: Hansen's disease, synonymously and commonly referred to as leprosy, is an important consideration when treating any chronic skin disorder and rheumatologic disorder. Personal clinical experience and a review of the literature highlight a lack of awareness for this disease by U.S. clinicians. In this country, accurate diagnosis is delayed. One cannot ensure swift and proper treatment without timely, accurate diagnosis. Unfortunately, severe debilitating nerve and tissue damage can occur within months. The authors draw upon recent personal and clinical experiences diagnosing and treating cases of the disease during a current resurgence in Florida. The authors aim to encourage readers to increase awareness for this ancient disease. In doing so, its relevance today and essential points in diagnosis and treatment are emphasized. This article is a compilation of our recent clinical experiences, in consultation with one of the world's leading authorities in the diagnosis and treatment of the disease and its complications: The National Hansen's Disease Program within the U.S. Department of Health and Human Services, Health Resources and Services Administration, Baton Rouge, Louisiana.